Enhancing Students’ Communication Skills through Problem Posing and Presentation - Sugito Sugito; Sri Mulyani Endang Susilowati; Hartono Hartono; Supartono Supartono (International Journal of Evaluation and Research in Education (IJERE), 2017)
This study was to explore how enhance communication skill through problem posing and presentation method.  The subjects of this research were the seven grade students Junior High School, including 20 male and 14 female. This research was conducted in two cycles and each cycle consisted of four steps, they were: planning, action, observation, and reflection. This study use interview, observation, and questionnaire to measure most widely used data gathering in communication skill students, and daily test (pre-test and post-test) to measure enhance achievement the students’. The data was analyzed comparing initial and final score. If the final score is better than initial score had been enhanced. Results of this study indicated that teaching and learning science used problem posing and presentation method can enhance ability communication skill, confidence, courage and responsibility on themselves disciples. Researcher is suggestion to use another method to enhance communication skill.